Advances in Komagataella phaffii Engineering for the Production of Renewable Chemicals and Proteins - Clara Vida Galrão Corrêa Carneiro; Luana Assis Serra; Thályta Fraga Pacheco; Letícia Maria Mallmann Ferreira; Lívia Teixeira Duarte Brandão; Mariana Nogueira de Moura Freitas; Débora Trichez; João Ricardo Moreira de Almeida (Fermentation, 2022)
The need for a more sustainable society has prompted the development of bio-based processes to produce fuels, chemicals, and materials in substitution for fossil-based ones. In this context, microorganisms have been employed to convert renewable carbon sources into various products. The methylotrophic yeast Komagataella phaffii has been extensively used in the production of heterologous proteins. More recently, it has been explored as a host organism to produce various chemicals through new metabolic engineering and synthetic biology tools. This review first summarizes Komagataella taxonomy and diversity and then highlights the recent approaches in cell engineering to produce renewable chemicals and proteins. Finally, strategies to optimize and develop new fermentative processes using K. phaffii as a cell factory are presented and discussed. The yeast K. phaffii shows an outstanding performance for renewable chemicals and protein production due to its ability to metabolize different carbon sources and the availability of engineering tools. Indeed, it has been employed in producing alcohols, carboxylic acids, proteins, and other compounds using different carbon sources, including glycerol, glucose, xylose, methanol, and even CO2.